The Ethnics Engagement: Navigating Power Dynamic and Ethnical Considerations in Community Based Education - Nahria Nahria; Tomi Apra Santosa; Dewanto Dewanto; Nurina Happy; Ifa Safira (Jurnal Medika: Medika, 2025)
social, cultural, and economic challenges faced by local communities(Yulianti, 2020); (Ali et al., 2024; Dewanto et al., 2023; Ichsan et al., 2023). This study examines ethnic involvement in community-based education by highlighting the power dynamics and ethical considerations that underlie the learning process and community empowerment. In the context of pluralistic community education, the involvement of ethnic groups is not only about participation, but also concerns bargaining positions, socio-cultural representation, and the challenges of maintaining justice and inclusivity. Through a qualitative approach based on literature studies and selected case studies, this study found that power inequality between education facilitators and local communities can hinder the process of social transformation. In addition, disregard for local values and norms often triggers resistance or misinterpretation of educational goals. Therefore, it is important to design a community-based educational approach that is sensitive to social dynamics, upholds participatory ethical principles, and strengthens community voices in decision-making. These findings recommend strengthening critical pedagogical practices that integrate local values with the goal of continuing education development.